Automatic Price Comparison Services: A global study - Heiko Genath; Tobias Brüggemann; Michael H. Breitner (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
Price comparison services are being used by more and more internet users worldwide to compare prices of (online-)suppliers. The characteristics of price comparison services differ internationally. Not only are they different in the reference to their scope of work. Also with regard to the technical performance or the definition of the revenue concepts great differences have been assessed. In the course of this essay criteria for global price comparison services are elaborated which are then consulted in conclusion for the construction of development categories. After reviewing of a variety of international price comparison services it turns out that classic concepts don't suffice in assessing development standards. A new concept is established which serves the global market analysis for successful price comparison services and those striving for progress. 50 countries with altogether over 230 price comparison services are classified and prospects and potentials are worked out. – – Preisvergleichsdienste werden weltweit von immer mehr Internetnutzern verwendet, um die Preise von verschiedenen (Online-) Anbietern zu vergleichen. International existieren verschiedene Ausprägungen von Preisvergleichsdiensten. Sie unterscheiden sich nicht nur im Bezug auf ihren Leistungsumfang. Auch im Hinblick auf die technische Umsetzung oder die Ausgestaltung der Erlöskonzepte sind Unterschiede festzustellen. Im Zuge dieser Arbeit werden Kriterien zum internationalen Vergleich von Preisvergleichsdiensten herausgearbeitet, die abschließend zur Erstellung von Entwicklungsklassen herangezogen werden. Es stellt sich nach der Überprüfung einer Vielzahl internationaler Preisvergleichsdienste heraus, dass klassische Konzepte zur Beurteilung von Entwicklungsniveaus hier nicht greifen. Ein neues Konzept wird erstellt, welches aktiven Preisvergleichsdiensten zur internationalen Marktanalyse dienen kann. 50 Nationen mit insgesamt über 230 Preisvergleichsdiensten werden auf dieser Basis eingestuft.
Keywords: O50; M21; F00; 330; Price comparison services; comparison shopping; e-commerce; internet economy; information-based and knowledge-based society